Analyzing The Impact of Electronic Card Adoption on The Profitability of The Iraqi Banking Sector (2017–2023)‎ - Halbous , Nuha Khalil; Abdulmahdi, Dr. Abdulkhleq Dubai (International Journal of Accounting and Economics Studies, 2025)
The rapid adoption of electronic cards has reshaped the Iraqi banking sector, influencing customer behavior, operational efficiency, and institutional performance. This study aims to analyze the impact of electronic card adoption on the profitability of Iraqi banks during the period ‎‎2017–2023. Using a theoretical framework supported by financial data analysis, the research investigates how digital payment channels ‎contribute to profitability through increased transaction volumes, reduced operational costs, and enhanced fee- and commission-based reve-‎nues. The findings indicate that electronic card usage has significantly expanded in Iraq, promoting financial inclusion and reducing reliance ‎on cash transactions. However, the growth in electronic cards has not been consistently matched by proportional increases in bank profitability, suggesting the need for more effective integration between digital payment expansion and revenue optimization strategies. This highlights the unstable relationship between card adoption and profitability, underlining the importance of strategic measures to translate digital ‎payment growth into tangible financial returns. The study provides practical insights for policymakers and banking institutions to enhance ‎operational efficiency, support financial inclusion, and ensure sustainable profitability amid Iraq’s ongoing digital transformation.
Keywords: Electronic Cards; Bank Profitability; Financial Inclusion; Operational Efficiency; Digital Transformation; Iraq